Kardiogeni šok - Poglajen, Gregor (Medicinski razgledi, 2009)
Cardiogenic shock is a state of tissue hypoperfusion that involves signs of progressive tissue injury due to failing heart function. Cardiogenic shock candevelop as a consequence of myocardial disease/injury, valve disease or heart rhythm disturbances. Most commonly, cardiogenic shock is a complication of acute myocardial infarction. Due to improved medical managment of advanced heart failure and methods of urgent rep er fusion of culprit coronary arteries, the incidence of cardiogenic shock and its mortality have declined in the last decade. However, about a half of patients with cardiogenic shock stili die. The diagnosis of cardiogenic shock is much more challenging than itseems. It is paramount that it is established quickly since timely intensivesupportive and etiologic treatment significantly impacts survival in patients with cardiogenic shock.
Keywords: Shock, Cardiogenic; Šok kardiogeni; Diagnosis; Miokardni infarkt; Dejavniki tveganja; Therapy; Mitralna zaklopka, insuficienca; Risk Factors; Myocardial Infarction; Aortna zaklopka, insuficienca; cardiovascular disease; Mitral Valve Insufficiency; kardiovaskularne bolezni; kardiogeni šok; Aortic Valve Insufficiency; srčni infarkt; patofiziologija; zdravljenje